Relationship Between Adverse Childhood Experiences, Glycaemic control, and Metabolic profile in Type 2 Diabetes Mellitus: a study in the Portuguese Population - Bárbara Sofia Fernandes Esteves (2021)
Background: Adverse childhood experiences (ACE) are highly prevalent in the general population. As a form of early psychological trauma, ACE alter metabolic, endocrine, and immunologic responses, and promote higher risk for several physical and psychiatric diseases in adulthood. A relationship has been reported between ACE and the diagnosis and control of type 2 Diabetes Mellitus (T2DM). This study goal was to evaluate the relationship between ACE, perceived stress, and clinical and laboratory profile in a group of T2DM patients. Methods: Sixty-six adult patients with T2DM were submitted to a psychosocial evaluation, and clinical and laboratory data were retrieved from the clinical charts. The occurrence of ACE and stress levels were measured with the Adverse Childhood Experiences Questionnaire - Short Version (ACEQ) and the Perceived Stress Scale (PSS-10); metabolic (HbA1c, glycemia, BMI, lipid, and tensional profile), health behaviours, and T2DM clinical outcomes were examined. Results: The mean age of the participants was 67.3 years (SD 10.5), the majority were males (65.2%), with a mean length of disease of 9.2 years. Forty-five reported at least one ACE. Participants presented a mean number of 2.4 (SD 2.57) ACE and a PSS-10 score of 15.1 (SD 7.38). From those presenting macro or microvascular lesions, 67.7% and 65.8%, respectively, reported ACE. A trend was found to higher HbA1c and glycaemia in patients with ACE; higher perceived stress was associated with poorer metabolic control. Conclusions: More severe clinical and laboratory parameters of T2DM were detected in patients who reported adverse experiences during childhood. Specific metabolic profile and higher stress levels found in this subgroup may indicate a dysfunctional endocrine response determined by early-life stressors.